MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS V SD NEGERI 009 AIR EMAS KECAMATAN UKUI - Tugino ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low result of fifth grade students learn math SD Negeri009 Air Emas. This study aims to improve learning outcomes with menerpakan mathematicaldemonstration methods. This research is a classroom action research, conducted over twocycles. Data used in the study are the data in student learning outcomes. The results statedthat results for students experiencing peningkata, this is evidenced by: At the beginning of thedata learning completeness students only 50% after repair in the first cycle increased to 70%and in cycle II to be increased to reach 85%.